2021
DOI: 10.1016/j.anl.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tongue-to-palate resistance training on tongue strength in healthy adults

Abstract: Tongue strength is crucial for safe and efficient oropharyngeal swallowing. This study examined the effect of tongue-to-palate resistance training (TPRT) on anterior and posterior tongue strength by conducting a prospective, randomized, parallel allocation trial.Methods: Ninety-one healthy adults were recruited in this study and were randomly assigned to an experimental group ( n = 44) or a control group ( n = 47). The experimental group performed TPRT for 8 weeks (5 days per week), whereas the control group p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 34 publications
1
36
0
7
Order By: Relevance
“…Anterior tongue muscles primarily contain fast-twitch muscles that might be easily influenced by aged-related sarcopenia [29]. However, tongue strengthening exercises can delay the atrophy of fast-twitch muscle fibers that occurs with aging [15,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anterior tongue muscles primarily contain fast-twitch muscles that might be easily influenced by aged-related sarcopenia [29]. However, tongue strengthening exercises can delay the atrophy of fast-twitch muscle fibers that occurs with aging [15,29].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, few research studies have reported tongue pressure and related factors in Chinese people [6,15]. Thus, healthcare providers require a comparative basis for the identification of altered tongue pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants received the same intervention protocol, which was based on guidelines for eating and the Taiwanese dysphagia care and guidance protocol [26], a tongue strength-training program [14], and an eating-ability promotion program [23]. There were three aspects covered by this intervention program.…”
Section: Multifaceted Intervention Programmentioning
confidence: 99%
“…The strength of the tongue to lift the bolus and push against the hard palate is critical to swallowing [13]. Many studies have confirmed that intensive training of the tongue muscle can enhance tongue muscle strength [14][15][16], preventing the effects of aging on swallowing function and improving the symptoms of dysphagia [17,18].…”
Section: Introductionmentioning
confidence: 99%